Analisis Desain Sambungan RBS Terprakualifikasi Pada Struktur Atap Gable Berdasarkan SNI 7972:2020 - Fahira, Najma; Hasyim, Wachid; Suhana, Nono (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Reduced Beam Section (RBS) joints generally reduce the plastic section of column-beam joints or column faces by reducing the flange width in the plastic joint area. The research compares the behavior and internal forces in the column-beam joints in conventional and Reduced Beam Section column-beam joints. The method used is a method of numerical analysis of research variables by standards and regulations. A notch with a reduction of 45% can be used as a first step in designing an RBS connection. The reduced beam section connection with a notch depth of 35 mm produces a maximum moment on the face of the column (Mf = 37800.466 Kgm) less than the plastic moment on the beam (ϕd Mpe = 44807.117 Kgm), The reduced beam section connection produces a shear force that occurs Vu = VRBS is (Vu = VRBS = 180.73 Kn) less than the allowable shear resistance (Vn = 280.8 kN), and the Reduced Beam Section (RBS) connection in the structure is more efficient than using conventional joints